Implementasi Ergostretch dan Administrative Control sebagai Multifaceted Ergonomic Intervention: Strategi Mitigasi Risiko Muskuloskeletal pada Teknisi Pest Control - Ryanta, Naufal Faryreza; Febriyanto, Kresna; Rosyidi, Ari Luthfi Rosyidi (Jurnal Anestesi, 2026)
Musculoskeletal Disorders (MSDs) are a persistent occupational health issue in the pest control sector due to intensive physical activity and non-neutral working postures. This study aims to evaluate the impact of ergonomic interventions that integrate educational, administrative, and physical aspects on MSDs risk among field technicians at CV. X Indonesia, Samarinda. Using a pre-post test design with a cross-sectional approach, this research involved 7 field technicians as subjects. Assessment instruments included the HIRADC method for hazard mapping, the Nordic Body Map (NBM) questionnaire to measure physical complaints, and work equipment evaluation based on biomechanical principles. Interventions implemented consisted of interactive safety briefings, the installation of educational posters, the development of ergonomic Standard Operating Procedures (SOPs), and a structured stretching program called ErgoStretch. Statistical analysis using the Paired Sample T-Test showed a significant increase in technicians’ knowledge scores by 45.63% (from a mean of 67.5 to 98.3 with p < 0.05). Qualitatively, the ErgoStretch program and SOP standardization successfully provided an immediate physiological impact by reducing muscle tension and improving working postures while operating heavy equipment such as thermal foggers. Although the overall ergonomic risk remains in the moderate category, this low-cost ergonomics strategy effectively created a more controlled work system and mitigated the risk of accumulating permanent injuries such as Carpal Tunnel Syndrome (CTS).